Optimization of diesel fuel components production using the model of interconnected hydrotreating and hydrodewaxing processes; Catalytic Hydroprocessing In Oil Refining - Ivanchina E. D. Emilia Dmitrievna; Belinskaya N. S. Natalia Sergeevna; Frantsina E. V. Evgeniya Vladimirovna; Popova N. V. Nataljya Vladimirovna (2016, 2016)
Title screen